Composite metal oxide catalyst, preparation method thereof and methane catalytic cracking method
By using composite metal oxide catalysts, the problems of high energy consumption of the catalyst, low methane conversion rate and low carbon product purity in the prior art are solved, and the production of low energy consumption, high conversion rate and high quality carbon nanotubes are achieved, which has high industrial application value.
Patent Information
- Application Number
- CN202311359828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
In the existing natural gas thermal catalytic cracking technology, the catalyst has high energy consumption, low methane conversion rate, low purity of carbon products produced, and limited economic benefits.
A composite metal oxide catalyst is used, which consists of a dehydrogenated main active component, a dehydrogenated co-active component and a support. The dispersion of the active metal is improved by a nonionic surfactant, the service life of the catalyst is extended, and the methane conversion rate and the quality of carbon nanotubes are improved.
It has achieved the production of low energy consumption, high methane conversion rate and high-quality carbon nanotubes, extends the service life of the catalyst, reduces production costs, and has high industrial application value.
Smart Images

Figure CN119857489A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of natural gas conversion and utilization and high-end carbon material preparation, and in particular to a composite metal oxide catalyst and a preparation method thereof and a methane catalytic cracking method. Background Art
[0002] The advantage of natural gas (CH4) thermal catalytic cracking hydrogen production and carbon material co-production technology is that one process produces two high value-added products, with low hydrogen production cost and zero carbon dioxide emissions during the reaction process. Therefore, compared with traditional coal-to-hydrogen production and natural gas steam reforming hydrogen production, it has more application and promotion value in the future low-carbon environment.
[0003] The CH4 molecule has a highly stable tetrahedral structure, and its CH bond energy is 434 kJ / mol. 3 The breaking of the hybrid CH bond is the most critical control step, with high activation energy. In the absence of a catalyst, the temperature required for CH4 kinetic cracking is 1200°C. In order to reduce the activation energy of the methane cracking reaction, researchers introduced catalysts, and different types of catalysts formed different types of carbon materials.
[0004] The research and development of natural gas thermal catalytic cracking hydrogen production catalysts is divided into four categories: (1) molten metal type; (2) composite metal oxide type; (3) metal alloy type; (4) composite carbon-based type. The reaction process using these four types of catalysts can achieve zero carbon emissions, but since the reaction is still an endothermic process, if fossil fuels are used for heating, the whole process will still have carbon dioxide emissions.
[0005] Each of these four types of catalysts has some problems. For example, the molten metal catalyst has a high methane conversion rate, but the space velocity is low, resulting in extremely slow carbon and hydrogen production efficiency per unit catalyst. The reaction process has high energy consumption, and the temperature needs to exceed 1000°C. It has stringent requirements on the reactor and high production and equipment investment costs. The energy consumption of solid alloy catalysts is slightly lower than that of molten salt catalysts. The reaction temperature is usually between 600-900°C and requires extremely low space velocity for reaction. Therefore, the carbon yield is low, and the carbon product morphology is mainly carbon black. Carbon-based catalysts produce carbon products with more metal impurities and carbon products, and the product purity is low. The energy consumption is similar to that of molten medium catalysts, and the catalyst activity cycle is short. The methane conversion rate of composite metal oxide catalysts is only lower than that of molten catalysts, but the service life is short and the methane conversion rate is low.
[0006] Patent CN114804023Y discloses a metal-molten salt preparation method and use for natural gas hydrogen production and carbon black, belonging to the field of methane cracking technology. The catalyst prepared by this method uses solid active metal porous nickel as an active non-supported catalyst, and the molten environment provided by the molten salt sodium chloride can make the generated carbon product float on the surface of the molten salt and can effectively reduce the impurities in the carbon product by water washing, acid washing, etc., to obtain a carbon black product with a purity of up to 99%, solving the problem of difficult separation of carbon products and low purity of carbon products. The molten salt used can be recycled and reused, and shows good catalytic performance for high-temperature methane cracking. The hydrogen conversion rate at a reaction temperature of 1000°C can reach more than 48%, and the obtained carbon product is carbon black with a purity of up to 99%. However, carbon black does not have high added value, the economic benefits it brings are limited, and this type of catalyst has high energy consumption.
[0007] Patent CN111689467Y discloses a method for producing hydrogen by catalyzing methane cracking with activated carbon as a catalyst. The method adopts a gas-solid phase catalytic reaction fixed bed reactor, takes methane as a raw material, adds a trace amount of hydrogen sulfide, takes activated carbon as a catalyst, reacts at 900-950°C and normal pressure, and obtains hydrogen and carbon products, wherein the concentration of hydrogen sulfide is 100ppm-300ppm. This method adds a trace amount of hydrogen sulfide to the methane feed gas, improves the activity of activated carbon catalyzing methane cracking to produce hydrogen, prolongs the deactivation time of the activated carbon catalyst, and has important industrial application value for improving the conversion efficiency of activated carbon catalyzing methane cracking to produce hydrogen. However, this type of carbon-based catalyst produces a large number of metal impurities and carbon products in the carbon product, and the product purity is low. The energy consumption is similar to that of the molten medium catalyst, and the catalyst activity cycle is short.
[0008] Therefore, it is necessary to provide a methane cracking catalyst with low reaction energy consumption, high methane conversion rate, the ability to produce high value-added products, and the ability to be applied to industrial production. Summary of the invention
[0009] In order to solve the above problems, the purpose of the present invention is to provide a composite metal oxide catalyst and a preparation method thereof and a methane catalytic cracking method. The composite metal oxide catalyst has high active metal dispersion and long service life, has a high methane conversion rate when applied to the methane cracking process, and the product carbon nanotubes are of good quality.
[0010] In order to achieve the above object, the present invention provides a composite metal oxide catalyst, wherein, based on the total mass of the catalyst being 100%, the catalyst comprises 10%-80% of a main dehydrogenation active component, 5%-50% of a dehydrogenation auxiliary active component, and the remainder being a carrier; the metal element in the dehydrogenation auxiliary active component is selected from one or a combination of two or more of the fourth period, the fifth period, and the sixth period and is selected from one or a combination of two or more of the IB group, the VB group, the VIB group, and the VIIB group; and / or, the metal element in the dehydrogenation auxiliary active component is selected from La-based metals;
[0011] The raw material of the composite metal oxide catalyst includes a non-ionic surfactant, and the mass ratio of the dehydrogenation main active component to the non-ionic surfactant is 1:3 to 1:6.
[0012] In the above-mentioned composite metal oxide catalyst, the main active component of dehydrogenation plays a major role in dehydrogenation and desulfurization and a major catalytic activity in methane cracking in the catalyst, and can improve the performance of other aspects of the catalyst. According to a specific embodiment of the present invention, the metal element in the main active component of dehydrogenation is selected from Group VIII of the fourth period, i.e., one or a combination of two or more of iron, cobalt, and nickel. Further, the metal element in the main active component of dehydrogenation may include cobalt. In some specific embodiments, the presence of the main active component of dehydrogenation in the catalyst may include metal elements and / or metal oxides. For example, the main active component of dehydrogenation may include cobalt elements and / or cobalt oxides.
[0013] The mass of the main active component of dehydrogenation is generally 10%-80% of the total mass of the catalyst, and can be further controlled to be 15%-50%. In some specific embodiments, the mass of the main active component of dehydrogenation can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% and other specific values of the total mass of the catalyst, as well as a range with any two of the above specific values as endpoints.
[0014] In the above composite metal oxide catalyst, the dehydrogenation auxiliary active component can improve the dispersibility and high temperature stability of the dehydrogenation main active component and improve the dehydrogenation activity of the catalyst.
[0015] In some specific embodiments, the mass of the dehydrogenation auxiliary active component is generally 5%-50% of the total mass of the catalyst, and can further be 14%-42%. In some specific embodiments, the mass of the dehydrogenation main active component can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% and other specific values of the total mass of the catalyst, and a range with any two of the above specific values as endpoints.
[0016] In the above-mentioned composite metal oxide catalyst, the metal elements in the dehydrogenation active component can play a role in improving the dispersibility of active sites and desulfurization ability, and can also assist in improving the performance of other aspects of the catalyst. The metal elements in the dehydrogenation active component may include La-based metals; and / or, the metal elements in the dehydrogenation active component may be selected from one or a combination of two or more of the following elements: elements of at least one group of IB group, VB group, VIB group, and VIIB group located in at least one period of the fourth period, the fifth period, and the sixth period. Specifically, the metal elements in the dehydrogenation active component may include one or a combination of two or more of La-based metals, copper, silver, gold, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, technetium, and rhenium. Further, the metal elements in the dehydrogenation active component include one or a combination of two or more of La, Cr, Mo, Ce, and Cu.
[0017] In the composite metal oxide catalyst, the dehydrogenation promoter component may exist in the catalyst in the form of a metal element and / or a metal oxide.
[0018] According to a specific embodiment of the present invention, the raw material of the composite metal oxide catalyst may include a nonionic surfactant. The nonionic surfactant can improve the dispersity of the active components in the catalyst, thereby improving the methane conversion rate and extending the life of the catalyst. Specifically, the nonionic surfactant can make the active metal dispersed more evenly in the solution, and the hydrophilic and hydrophobic groups in the nonionic surfactant wrap small solution particles. While contacting the precipitant, the active components can be dispersed to the maximum extent, and the uniformity of the active metal in the catalyst can be improved, thereby increasing the loading amount of the metal in the catalyst and reducing the occurrence of a low loading amount of the active metal in the catalyst. In some specific embodiments, the nonionic surfactant includes one or more combinations of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester and polyoxyethylene alkylamine. The fatty alcohol polyoxyethylene ether may include AEO-7, the fatty acid polyoxyethylene ester may include OEO-A-105, and the alkylphenol polyoxyethylene ether may include polyoxyethylene lauryl ether.
[0019] According to a specific embodiment of the present invention, the carrier and the non-ionic surfactant can improve the dispersion of the active components in the catalyst system (including the main active component of dehydrogenation and the auxiliary active component of dehydrogenation), prevent the active components from agglomerating, and thus improve the service life of the catalyst, the methane conversion rate and the quality of the output carbon nanotubes, providing convenience for future scale-up production.
[0020] According to a specific embodiment of the present invention, the mass ratio of the dehydrogenation main active component to the nonionic surfactant is generally controlled to be 1:3 to 1:6. In some specific embodiments, the mass ratio of the dehydrogenation main active component to the nonionic surfactant can be controlled to be 1:3, 1:4, 1:5, 1:6, and other specific values, as well as a range with any two of the above specific values as endpoints.
[0021] In the above composite metal oxide catalyst, the catalyst further comprises 5%-40% of a secondary active component, based on the total mass of the catalyst being 100%. The secondary active component can synergistically improve the dehydrogenation activity of the catalyst with the dehydrogenation co-active component and the carrier, extend the service life of the catalyst, improve the value and quality of the cracking product (such as carbon nanotubes), and reduce the energy consumption of the device. Accordingly, the raw material for preparing the catalyst may also include a precursor of the secondary active component.
[0022] In some specific embodiments, the mass of the secondary active component is generally 5%-40% of the total mass of the catalyst, and can further be 20%-35%. In some specific embodiments, the mass of the secondary active component can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% and other specific values of the total mass of the catalyst, and a range with any two of the above specific values as endpoints.
[0023] In the above-mentioned composite metal oxide catalyst, the metal element in the secondary active component generally has methane cracking activity and can enhance the activity of the catalyst. In the periodic table, the metal element in the secondary active component is a VIII group in at least one of the fourth period, the fifth period, and the sixth period; that is, the period in which the metal element in the secondary active component is located includes one or more combinations of the fourth period, the fifth period, and the sixth period, and the group in which the metal element in the secondary active component is located includes the VIII group. Specifically, the metal element in the secondary active component includes one or more combinations of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum. More specifically, the metal element in the secondary active component includes one or more combinations of Fe, Ni, Pd, Pt and Ru.
[0024] In the above composite metal oxide catalyst, the side active components may exist in the catalyst in the form of metal elements and / or metal oxides.
[0025] In the above-mentioned composite metal oxide catalyst, the carrier may include an inert carrier and / or an inert dispersible metal additive. The carrier includes the following components and / or a composite oxide formed by the following components: TiO2, ZrO2, γ-Al2O3, SiO2, MgO, CaO, zinc aluminum spinel, nickel aluminum spinel, magnesium aluminum spinel, calcium aluminum spinel, perovskite, titanium silicon molecular sieve, mullite and silicon carbide, one or a combination of two or more thereof; for example, the carrier may include a composite oxide formed by at least two of TiO2, ZrO2, γ-Al2O3, SiO2, MgO and CaO; more specifically, the carrier may include γ-Al2O3, MgO, magnesium aluminum spinel, SiO2, ZrO2 and perovskite, one or a combination of two or more thereof. Compared with conventional carriers such as vermiculite, the above-mentioned types of carriers used in the present invention have high hardness, which can avoid the problem of crushing when applied to fluidized bed processes. Moreover, compared with conventional carriers, spinel carriers (zinc aluminum spinel, nickel aluminum spinel, magnesium aluminum spinel, calcium aluminum spinel, etc.) and perovskite have better dispersibility.
[0026] According to a specific embodiment of the present invention, based on the total mass of the catalyst as 100%, the composite metal oxide catalyst includes 10%-80% of a main dehydrogenation active component (preferably 15%-50%), 5%-50% of a dehydrogenation auxiliary active component (preferably 14%-42%), 5%-40% of a secondary active component (preferably 20-35%), and the remainder is a carrier.
[0027] According to a specific embodiment of the present invention, based on the total mass of the catalyst as 100%, the composite metal oxide catalyst includes 15%-50% of a main dehydrogenation active component, 14%-42% of a dehydrogenation auxiliary active component, 20%-35% of a secondary active component, and the remainder is a carrier.
[0028] Conventional composite metal oxide catalysts have a short life span of only 20-50 minutes. The present invention adds a dehydrogenation main active component (cobalt) and a dehydrogenation auxiliary active component (molybdenum, copper, etc.) to the catalyst, utilizing the characteristics of long catalytic life of cobalt and the anti-agglomeration property (especially anti-agglomeration property of cobalt and nickel) of the dehydrogenation auxiliary active component, so that the life span of the synthesized composite metal oxide catalyst is significantly improved. When the dehydrogenation auxiliary active component contains nickel, the cobalt catalyst itself can have the methane cracking properties of the two, so that the methane conversion rate of the composite metal oxide catalyst is also maintained at a good level.
[0029] The present invention utilizes the good intercalation between the carrier and the main dehydrogenation active component and the auxiliary dehydrogenation active component (such as magnesium aluminum spinel and cobalt, magnesium oxide and aluminum oxide and nickel active groups) during the crystal formation process, and can efficiently dope the main dehydrogenation active component and the auxiliary dehydrogenation active component into the inert carrier, thereby solving the technical problem that the active component is difficult to enter the main skeleton of the catalyst. At the same time, the active component has a high dispersion, thereby improving the conversion rate of methane in the catalyst reaction process.
[0030] In the above composite metal oxide catalyst, the raw materials for preparing the composite metal oxide catalyst further include a precipitant. The composite metal oxide catalyst can be obtained by a precipitation reaction of the raw materials for preparing the composite metal oxide catalyst.
[0031] The present invention also provides a method for preparing the composite metal oxide catalyst, the preparation method comprising:
[0032] The precursor of the carrier, the precursor of the dehydrogenation auxiliary active component, the precursor of the dehydrogenation main active component, and the non-ionic surfactant are mixed to form a raw material solution;
[0033] The precipitant is added dropwise to the raw material solution to form a reaction solution, or the raw material solution and the precipitant are added dropwise in parallel to form a reaction solution; the reaction solution is precipitated, and after the precipitation is complete (the precipitant is added dropwise), it is aged, dried, and calcined to obtain a composite metal oxide catalyst.
[0034] In the above preparation method, the precursor of the main active component of dehydrogenation is generally a metal salt, which can specifically include one or a combination of two or more of metal nitrates, metal phosphates, and metal sulfates. More specifically, the precursor of the main active component of dehydrogenation can include one or a combination of two or more of cobalt nitrate, cobalt phosphate, and cobalt sulfate.
[0035] In the above preparation method, the precursor of the dehydrogenation auxiliary active component includes a metal salt and / or a metal oxide. When the dehydrogenation auxiliary active component includes a metal salt, the metal salt includes one or a combination of two or more of metal nitrates, metal phosphates, and metal sulfates. That is, the precursor of the dehydrogenation auxiliary active component includes one or a combination of two or more of metal nitrates, metal phosphates, metal sulfates, and metal oxides. Specifically, the precursor of the dehydrogenation auxiliary active component includes one or a combination of two or more of lanthanum nitrate, phosphotungstic acid, silver nitrate, copper nitrate, manganese nitrate, and Nb2O5.
[0036] In the above preparation method, the precursor of the carrier may also include one or a combination of two or more of metal nitrates, metal phosphates, and metal sulfates.
[0037] In the above preparation method, the precipitant includes one or a combination of two or more of ammonia water, sodium hydroxide, potassium hydroxide, ammonium bicarbonate or ammonium carbonate. Further, the precipitant includes ammonium bicarbonate. In some specific embodiments, the precipitant can be added in the form of a precipitant solution. More specifically, the concentration of the precipitant solution can be 0.01-0.2 mol / L, and can be further controlled to be 0.05-0.1 mol / L.
[0038] In the above preparation method, the precipitation process may include a stirring operation, and the stirring speed may be 300-550r / min. Specifically, the stirring speed may be 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min and other specific values, as well as a range with any two of the above specific values as endpoints.
[0039] In the above preparation method, by controlling the reaction time, the catalyst yield can be increased; by controlling the aging time, the reactants can be fully precipitated and the precipitation can be more complete. The precipitation temperature can be 60-90°C, and further can be 70-85°C. The aging temperature is 60-90°C, and further can be 70-85°C; the aging time is 4-12h, and further can be 6-8h. After the feeding is completed, by keeping the precipitation and aging temperatures consistent, the crystallization conditions can be stabilized to the maximum extent, which is beneficial to maintaining the crystallization stability and improving the regularity of the crystals. At the same time, controlling the stirring speed during the precipitation process and the aging process at 300-550r / min can control the size of the crystals, which is beneficial to the subsequent application of the catalyst in the fluidized bed.
[0040] In the above preparation method, the aging can be carried out in a static aging manner; alternatively, the aging process can also include a stirring operation, and stirring can improve the crystallization effect of the reaction solution. In some specific embodiments, the stirring speed can be 300-550r / min, specifically, the stirring speed can be 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min and other specific values, as well as a range with any two of the above specific values as endpoints.
[0041] In the above preparation method, the specific manner of forming the reaction solution may include: dripping the precipitant into the raw material solution to form the reaction solution, or dripping the raw material solution and the precipitant in parallel to form the reaction solution. In some specific embodiments, compared with the manner of dripping the precipitant into the raw material solution, the manner of dripping the raw material solution and the precipitant in parallel to form the reaction solution can obtain a more suitable contact concentration, which can improve the crystallization efficiency of the metal, promote the rapid crystallization of the active metal, and increase the catalyst yield; and the manner of dripping the raw material solution and the precipitant in parallel can further improve the component uniformity in the catalyst compared with the manner of dripping the precipitant into the raw material solution, and at the same time improve the dispersion of the active metal in the catalyst.
[0042] In the above preparation method, the drop speed of the raw material solution and / or the precipitant can be controlled to be 60-600ml / h, and further can be controlled to be 300-500ml / h. In some specific embodiments, the above drop speed can be specifically controlled to be 60ml / h, 100ml / h, 150ml / h, 200ml / h, 250ml / h, 300ml / h, 350ml / h, 400ml / h, 450ml / h, 500ml / h, 550ml / h, 600ml / h and other specific values and the range with any two of the above specific values as endpoints. Controlling the drop speed can effectively control the contact time of the precipitant with the raw material solution and improve the crystallization stability.
[0043] In the above preparation method, the pH value of the reaction solution can be controlled to be 9 to 10. By controlling the pH value of the reaction solution within a certain range, the complete precipitation of the raw materials can be promoted.
[0044] In the above preparation method, the drying temperature is 80-150° C., and the drying time is 1-24 hours.
[0045] In the above preparation method, the calcination temperature is generally 600-1000°C, and can be further controlled to be 650-800°C; the calcination time is 0.1-10h, and can be further controlled to be 2-6h.
[0046] The dispersion effect of active metals in composite metal oxide catalysts synthesized by conventional precipitation methods is not good, and the synthesized catalysts often have complex large-size active metal grains, with few effective active sites of the catalyst exposed and low reaction activity. In the present invention, by controlling the precipitation temperature, pH value, aging conditions (including aging temperature and aging time), and combining the dispersing aid (dehydrogenation auxiliary active component) with a non-ionic surfactant, a high-concentration active metal solution (generally a precursor solution of the main active component of dehydrogenation) is treated with a non-ionic surfactant in advance, and a precipitant is added dropwise to the high-concentration solution to promote the formation of highly dispersed active metal grains, greatly increase the active site content in the composite metal oxide catalyst, and help improve the methane processing capacity of the catalyst and the efficiency of the catalyst in cracking methane. The high dispersion of active metal grains can promote the formation of high-quality carbon nanotubes.
[0047] In the above preparation method, the raw material solution can be formed by mixing a first solution and a second solution, wherein the first solution includes a precursor of a carrier and a precursor of a dehydrogenation auxiliary active component, and the second solution includes a precursor of a dehydrogenation main active component and a nonionic surfactant. The precursor of the dehydrogenation main active component and the nonionic surfactant form the second solution, so that the surfactant can fully wrap the precursor of the dehydrogenation main active component and improve the dispersion degree of the dehydrogenation main active component.
[0048] In the above preparation method, a high concentration of the precursor solution of the main active component of dehydrogenation (the concentration is generally 30-80 g / L) is treated with a non-ionic surfactant to form a second solution, and then a precipitant is added to the second solution, which can promote the formation of highly dispersed active metal grains. Accordingly, the above preparation method can specifically include:
[0049] S1, mixing a precursor of a carrier and a precursor of a dehydrogenation-promoting active component to form a first solution;
[0050] S2, mixing a precursor of a dehydrogenation main active component and a nonionic surfactant to form a second solution;
[0051] S3, mixing the first solution and the second solution to form a raw material solution, mixing the raw material solution with a precipitant to form a reaction solution, precipitating the reaction solution, aging, drying, and calcining after the precipitation is complete to obtain a composite metal oxide catalyst.
[0052] According to a specific embodiment of the present invention, when the composite metal oxide catalyst includes a secondary active component, correspondingly, the raw material solution may also include a precursor of the secondary active component.
[0053] In the existing synthesis methods, when active metal atoms are doped into another metal oxide system, due to the limitations of the synthesis conditions, the metal is very likely to cluster or be unevenly dispersed in the region. The above-mentioned composite metal oxide preparation method provided by the present invention can efficiently disperse the active components into an inert carrier, and use the stable crystal structure formed by the carrier as the main skeleton of the catalyst to anchor the active components, thereby reducing the agglomeration of the active components during the reaction. The introduction of the dual active components formed by the dehydrogenation main active component and the secondary active component and the high dispersion possessed are conducive to improving the catalyst's ability to produce hydrogen and carbon nanotubes. In some specific embodiments, the precursor of the secondary active component can be added simultaneously with the precursor of the dehydrogenation main active component.
[0054] In the above preparation method, the precursor of the secondary active component and the dehydrogenation main active component can be added simultaneously with a nonionic surfactant, and the nonionic surfactant is used to improve the distribution of the active component. Specifically, the precursor of the secondary active component can be included in the second solution together with the dehydrogenation main active component and the nonionic surfactant.
[0055] In the above preparation method, the mass of the nonionic surfactant can be 1%-30% of the mass of the second solution, and can be further controlled to be 5%-20%. In some specific embodiments, the mass of the nonionic surfactant can be 1%, 3%, 5%, 7%, 8%, 10%, 13%, 15%, 18%, 20% of the mass of the second solution, and a range with any two of the above specific values as endpoints.
[0056] In the above preparation method, the precursor of the secondary active component includes one or more combinations of metal salts, metal hydroxides, and metal oxides. Specifically, when the precursor of the secondary active component includes a metal salt, the metal salt includes one or more combinations of metal carbonates, metal nitrates, metal sulfates, metal phosphates, and metal chlorates. In some specific embodiments, the precursor of the secondary active component includes one or more combinations of Fe(NO3)3, Ni(NO3)2, and PtCl4.
[0057] It can be understood that the dosage of the precursor of the dehydrogenation main active component, the precursor of the secondary active component, the precursor of the dehydrogenation auxiliary active component and the precursor of the carrier can be determined according to the mass content of the dehydrogenation main active component, the secondary active component, the dehydrogenation auxiliary active component and the carrier in the above-mentioned composite metal oxide catalyst.
[0058] In the above preparation method, in S1, the mixing temperature is 55-95° C., and can be further controlled to be 70-90° C. In some specific embodiments, the mixing temperature can be specific values such as 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., and a range with any two of the above specific values as endpoints.
[0059] According to a specific embodiment of the present invention, in S1, the mixing process includes a stirring operation, and the stirring speed is 300-700 r / min, preferably 400-600 r / min.
[0060] In the above preparation method, in S2, the mixing temperature is 55-95° C., and can be further controlled to be 70-90° C. In some specific embodiments, the mixing temperature can be specific values such as 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., and a range with any two of the above specific values as endpoints.
[0061] According to a specific embodiment of the present invention, in S2, the mixing process includes a stirring operation, and the stirring speed is 300-700 r / min, and can be further controlled to 400-600 r / min.
[0062] According to a specific embodiment of the present invention, the preparation method of the composite metal oxide catalyst comprises:
[0063] S1, stirring the precursor of the carrier and the precursor of the dehydrogenation active component (preferably at a speed of 300-700 r / min, more preferably 400-600 r / min) at 55-95° C. (preferably 70-90° C.) to form a first solution;
[0064] S2, mixing the precursor of the main active component of dehydrogenation and the precursor of the secondary active component to form a mixed solution, adding a nonionic surfactant to the mixed solution (the dropping speed is preferably 50-300 ml / h, more preferably 100-200 ml / h), stirring and mixing to form a second solution; the stirring speed is preferably 300-700 r / min, more preferably 400-600 r / min, and the mixing temperature is preferably 55-95° C., more preferably 70-90° C.;
[0065] S3, dropwise adding a precipitant solution (preferably at a concentration of 0.01-0.2 mol / L, more preferably 0.05-0.1 mol / L) to a raw material solution formed by mixing the first solution and the second solution to form a reaction solution, wherein the dropping speed of the precipitant solution is preferably 60-600 ml / h, more preferably 300-500 ml / h; or, dropwise adding the precipitant solution and the raw material solution in parallel to form a reaction solution, wherein the dropping speed of the parallel flow is preferably 60-600 ml / h, more preferably 300-500 ml / h; the reaction solution is precipitated at 60-90° C. (preferably 70-85° C.), and stirred during the precipitation process (the stirring speed is preferably 300-550 r / min);
[0066] The reaction solution after precipitation is aged (the temperature is preferably 60-90°C, more preferably 70-85°C; the time is preferably 4-12h, more preferably 6-8h), stirred during the aging process (the speed is preferably 300-550r / min), dried (the temperature is preferably 80-150°C; the time is preferably 1-24h), and calcined (the temperature is preferably 600-1000°C, more preferably 650-800°C; the time is preferably 0.1-10h, more preferably 2-6h) to obtain a composite metal oxide catalyst.
[0067] The present invention also provides a methane catalytic cracking method, wherein the catalyst used in the methane catalytic cracking method includes the composite metal oxide catalyst provided by the present invention. The composite metal oxide catalyst provided by the present invention can prepare cracking products such as carbon nanotubes and hydrogen when applied to methane catalytic cracking through the synergistic effect between the main dehydrogenation active component, the dehydrogenation auxiliary active component and the carrier (optionally including a secondary active component), and has the characteristics of low required reaction temperature, high catalytic activity, long service life, good thermal stability, and high quality of the output carbon nanotubes.
[0068] In the above-mentioned methane catalytic cracking method, the reaction process of methane catalytic cracking can be as follows: first, methane is adsorbed on the surface of the catalyst, and the CH bond breaks under certain conditions, among which the cracking of the methane tetrahedron is the most critical and is the control step of the reaction; secondly, after the CH bond breaks, H is converted into molecular form to form the primary product H2; the next step is that carbon is adsorbed on the surface of the active site of the catalyst to form a carbon core, and different carbon materials are formed through the diffusion-storage-precipitation steps of the carbon core inside the active metal. Generally speaking, the type of carbon material is related to the type of catalyst, and the catalyst provided by the present invention can produce high-quality carbon nanotubes.
[0069] According to a specific embodiment of the present invention, the composite metal oxide catalyst provided by the present invention can efficiently catalyze the cracking of methane to produce hydrogen and carbon nanotubes at a relatively low temperature. In the above-mentioned methane catalytic cracking method, the methane feed flow rate is 50-300ml / min, which can be further controlled to 150-250ml / min; the reducing gas concentration is 5-80%, which can be further controlled to 10-45%; the reduction temperature is 300-900℃, which can be further controlled to 550-750℃; the reaction temperature is 500-800℃, which can be further controlled to 550-750℃, and further controlled to 600-700℃. The cracking products obtained by the above-mentioned methane catalytic cracking method may include carbon nanotubes and hydrogen. In some specific embodiments, the carbon nanotubes may be multi-walled carbon nanotubes, and the diameter of the multi-walled carbon nanotubes may be 10nm-20nm and the length may be 10μm-20μm.
[0070] According to a specific embodiment of the present invention, the reducing gas may include hydrogen or the like.
[0071] According to a specific embodiment of the present invention, the reduction method adopted in the methane catalytic cracking method can be constant temperature reduction or synchronous temperature rise reduction.
[0072] According to a specific embodiment of the present invention, the methane catalytic cracking method can be achieved by a vapor deposition reaction. In some specific embodiments, the vapor deposition reaction can be carried out in a horizontal tube heating furnace.
[0073] According to a specific embodiment of the present invention, in the above-mentioned methane catalytic cracking method, the life of the catalyst can reach 5h-14h.
[0074] The beneficial effects of the present invention include:
[0075] 1. The composite metal oxide catalyst provided by the present invention has high active metal dispersion, low required reaction temperature, mild reaction conditions, high product unit catalyst yield, and easy industrial scale-up. The composite metal oxide catalyst has high methane conversion rate, long service life, good thermal stability, high quality of output carbon nanotubes, low required energy consumption and high production capacity, and has high industrial scale-up application value. It can be applied to fluidized bed and moving bed reactors, which can save costs for future industrial applications.
[0076] 2. The methane catalytic cracking method provided by the present invention utilizes the composite metal oxide catalyst to realize large-scale and inexpensive preparation of hydrogen and carbon nanotubes. The catalyst can overcome the problems of low methane single-pass conversion rate, low production capacity, and difficulty in balancing the contradiction between environmental protection and economic benefits in carbon deposit utilization in the prior art. While efficiently catalytically cracking methane, the generated carbon deposits can be effectively utilized, thereby achieving the effect of reducing energy consumption, reducing CO2 emissions, and improving environmental protection and economic win-win results. The catalyst can be applied to a device for producing hydrogen from methane catalytic cracking in a circulating fluidized bed reactor and a regenerator, meeting the needs of continuous reaction-regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1a This is the mapping characterization result of the Ni element of the composite metal oxide catalyst in Example 1.
[0078] Figure 1b This is the mapping characterization result of the Co element of the composite metal oxide catalyst in Example 1.
[0079] Figure 2 It is a dark field transmission electron microscope image and element linear scanning image of the composite metal oxide catalyst of Example 1.
[0080] Figure 3a This is a SEM image of the methane cracking product obtained using the catalyst of Example 1.
[0081] Figure 3b TEM image of methane cracking product obtained using the catalyst of Example 1.
[0082] Figure 4a , Figure 4b This is the crystal surface characterization result of the catalyst in Example 1.
[0083] Figure 5a This is the mapping characterization result of the Ni element of the composite metal oxide catalyst of Comparative Example 3.
[0084] Figure 5b This is the mapping characterization result of the Co element of the composite metal oxide catalyst of Comparative Example 3. DETAILED DESCRIPTION
[0085] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0086] The XRF used in the following examples and comparative examples tests the content of each element component in the solid material (in terms of oxide).
[0087] Example 1
[0088] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0089] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Add 1.2 g of ammonium molybdate tetrahydrate, 2.6 g of magnesium nitrate hexahydrate, 2.4 g of aluminum nitrate nonahydrate, 0.7 g of copper nitrate trihydrate, 0.8 g of lanthanum nitrate hexahydrate, 0.1 g of cerium nitrate hexahydrate and 0.6 g of chromium nitrate nonahydrate into the water and stir thoroughly at 80°C to obtain the first solution.
[0090] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 3.2 g of nickel nitrate hexahydrate, 1.4 g of cobalt nitrate hexahydrate, and 5 g of polyoxyethylene lauryl ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0091] 3. The first solution and the second solution were dripped into a 2L three-necked flask to obtain a raw material solution; 11g of ammonium bicarbonate was dissolved in 550ml of water to obtain a precipitant solution, and the precipitant solution was dripped into the raw material solution at a speed of 450ml / h (peristaltic pump speed was 7) until the precipitant solution was completely dripped to obtain a reaction solution, the pH value of the reaction solution was 9-10, and stirring was continued at 85°C until precipitation was complete;
[0092] 4. The reaction solution after precipitation was kept warm (85°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the drying temperature was set to 110°C. After drying, the solid was crushed with a mortar, sieved with an 80-mesh screen, and the sieved solid was calcined at 800°C for 5 hours to obtain 2.76g of the target catalyst.
[0093] Calculated by the mass content of metal oxides, the catalyst contains 20% cobalt, 30% nickel, 6% lanthanum, 2% chromium, 2% cerium, 8% copper, 15% magnesium, 12% aluminum and 5% molybdenum.
[0094] Example 2
[0095] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0096] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Add 2.1 g of magnesium nitrate hexahydrate, 2 g of aluminum nitrate nonahydrate, 0.5 g of copper nitrate trihydrate, 0.4 g of lanthanum nitrate hexahydrate, 0.2 g of cerium nitrate hexahydrate and 0.1 g of chromium nitrate nonahydrate into the water and stir thoroughly at 80°C to obtain the first solution.
[0097] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 1 g of cobalt nitrate hexahydrate, 3 g of nickel nitrate hexahydrate, and 5 g of polyoxyethylene lauryl ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0098] 3. Add the first solution and the second solution to a large beaker to obtain a raw material solution. Then take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Pour 100ml of the precipitant solution as the base liquid into a 2L three-necked flask, add the raw material solution and the precipitant solution to the base liquid at a rate of 450ml / h (peristaltic pump speed is 7) until the two liquids are completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10, and the solution is stirred continuously at 85°C until the precipitation is complete.
[0099] 4. The reaction solution after precipitation was kept warm (85°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 2.19g of the target catalyst.
[0100] Calculated by the mass content of metal oxides, the catalyst contains 20% cobalt, 35% nickel, 6% lanthanum, 2% chromium, 2% cerium, 8% copper, 15% magnesium and 12% aluminum.
[0101] Comparative Example 1
[0102] This comparative example provides a composite metal oxide catalyst, the preparation method of which comprises:
[0103] 1. Use a measuring cylinder to take 400 mL of water and put it into a small beaker. Then add 3.1 g of nickel sulfate hexahydrate, 1.5 g of ammonium molybdate tetrahydrate, 2.8 g of magnesium sulfate hexahydrate, 2.8 g of aluminum sulfate nonahydrate, 0.9 g of copper sulfate trihydrate, 0.5 g of chromium sulfate and 8 g of alkylphenol polyoxyethylene ether, and stir well at 80 ° C to obtain a raw material solution.
[0104] 2. Take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Pour 100ml of the precipitant solution as the base liquid into a 2L three-necked flask, and add the raw material solution and the precipitant solution to the base liquid at a rate of 450ml / h (peristaltic pump speed is 7) in parallel until the two liquids are completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10, and the solution is stirred continuously at 85°C until precipitation is complete.
[0105] 3. The reaction solution after precipitation was kept warm (85°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 2.8g of the target catalyst.
[0106] Calculated by the mass content of metal oxides, the catalyst contains 37% nickel, 8% chromium, 13% copper, 20% magnesium, 17% aluminum and 5% molybdenum.
[0107] Example 3
[0108] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0109] 1. Use a measuring cylinder to take 400 mL of water and put it into a small beaker, then add 2.5 g of nickel nitrate hexahydrate, 1.2 g of cobalt nitrate hexahydrate, 1.2 g of ammonium molybdate tetrahydrate, 2.3 g of magnesium nitrate hexahydrate, 1.8 g of aluminum nitrate nonahydrate, 0.8 g of copper nitrate trihydrate, 0.3 g of calcium nitrate tetrahydrate, 0.3 g of ferric nitrate nonahydrate and 5 g of fatty alcohol polyoxyethylene ether (AEO-7), stir well at 80 ° C to obtain a raw material solution, and pour the raw material solution into a 2L three-necked flask.
[0110] 2. Take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Add the precipitant solution to the raw material solution at a rate of 450ml / h (peristaltic pump speed is 7) until the precipitant solution is completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10. Stir continuously at 85°C until precipitation is complete.
[0111] 3. The reaction solution with complete precipitation was kept warm (85°C) for aging for 4 hours, and then the reaction solution was placed in an electric constant temperature blast drying oven for drying for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 2.41g of the target catalyst.
[0112] Calculated by the mass content of metal oxides, the catalyst contains 27% nickel, 15% cobalt, 7% iron, 6% calcium, 6% chromium, 9% copper, 15% magnesium, 10% aluminum and 5% molybdenum.
[0113] Example 4
[0114] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0115] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 0.5 g of ammonium molybdate tetrahydrate, 3.3 g of magnesium nitrate hexahydrate, 2.6 g of aluminum nitrate nonahydrate and 0.6 g of copper nitrate trihydrate respectively, and stir thoroughly at 80°C to obtain the first solution.
[0116] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 2 g of cobalt nitrate hexahydrate and 10 g of fatty acid polyoxyethylene ester (OEO-A-105) respectively, and stir thoroughly at 80°C to obtain a second solution.
[0117] 3. Pour the first solution and the second solution into a 2L three-necked flask to obtain a raw material solution. Then take 11g of citric acid and dissolve it in 550ml of water to obtain a precipitant solution. Add the precipitant solution to the raw material solution at a rate of 450ml / h (peristaltic pump speed is 7) until the precipitant solution is completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10. Stir continuously at 85°C until precipitation is complete.
[0118] 4. The reaction solution after precipitation was kept warm (85°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 1.68g of the target catalyst.
[0119] Calculated by the mass content of metal oxides, the catalyst contains 34% cobalt, 21% aluminum, 11% copper, 31% magnesium and 3% molybdenum.
[0120] Comparative Example 2
[0121] This comparative example provides a composite metal oxide catalyst, the preparation method of which comprises:
[0122] 1. Use a measuring cylinder to take 400 mL of water and put it into a small beaker. Then add 1.8 g of nickel nitrate hexahydrate, 1.4 g of cobalt nitrate hexahydrate, 1.7 g of ammonium molybdate tetrahydrate, 5.7 g of magnesium nitrate hexahydrate, and 0.8 g of copper nitrate trihydrate, respectively. Stir well at 80 ° C to obtain a raw material solution, and pour the raw material solution into a 2L three-necked flask.
[0123] 2. Take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Add the precipitant solution to the raw material solution at a rate of 450ml / h (peristaltic pump speed is 7) until the precipitant solution is completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10. Stir continuously at 85°C until precipitation is complete.
[0124] 3. The reaction solution after precipitation was kept warm (85°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 2.19g of the target catalyst.
[0125] Calculated by the mass content of metal oxides, the catalyst contains 21% nickel, 18% cobalt, 11% copper, 41% magnesium and 9% molybdenum.
[0126] Example 5
[0127] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0128] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 4.7 g of aluminum nitrate nonahydrate, 0.9 g of copper nitrate trihydrate, 0.3 g of cerium nitrate hexahydrate, and 1.2 g of chromium nitrate nonahydrate respectively, and stir thoroughly at 80°C to obtain the first solution.
[0129] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 2.2 g of nickel nitrate hexahydrate, 1.7 g of ferric nitrate nonahydrate, 1.5 g of cobalt nitrate hexahydrate and 5 g of polyoxyethylene lauryl ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0130] 3. Pour the first solution and the second solution into a 2L three-necked flask to obtain a raw material solution. Then take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Add the precipitant solution to the raw material solution at a rate of 450ml / h (peristaltic pump speed is 7) until the precipitant solution is completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10, and the solution is stirred continuously at 85°C until precipitation is complete.
[0131] 4. The reaction solution after precipitation was kept warm (85°C) for 4 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 2.77g of the target catalyst.
[0132] Calculated by the mass content of metal oxides, the catalyst contains 20% nickel, 15% cobalt, 18% iron, 23% aluminum, 11% copper, 5% cerium and 8% chromium.
[0133] Comparative Example 3
[0134] This comparative example provides a composite metal oxide catalyst, the preparation method of which comprises:
[0135] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 5.1 g of aluminum nitrate nonahydrate, 0.8 g of copper nitrate trihydrate, 0.5 g of cerium nitrate hexahydrate, and 0.7 g of chromium nitrate nonahydrate respectively, and stir thoroughly at 80°C to obtain the first solution.
[0136] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 1.9 g of nickel nitrate hexahydrate, 1.5 g of ferric nitrate nonahydrate and 2.1 g of cobalt nitrate hexahydrate respectively, and stir thoroughly at 80°C to obtain a second solution.
[0137] 3. Pour the first solution and the second solution into a 2L three-necked flask to obtain a raw material solution. Then take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Add the precipitant solution to the raw material solution at a rate of 450ml / h (peristaltic pump speed is 7) until the precipitant solution is completely added to obtain a reaction solution. The pH value of the reaction solution is 9-10, and the solution is stirred continuously at 85°C until precipitation is complete.
[0138] 4. The reaction solution after precipitation was kept warm (85°C) for 4 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 2.31g of the target catalyst.
[0139] In terms of metal oxide mass content, the catalyst contains 18% nickel, 21% cobalt, 14% iron, 25% aluminum, 9% copper, 8% cerium and 5% chromium. Comparing this comparative example with Example 5, it can be seen that by adding a nonionic surfactant during the preparation process, the hydrophilic and hydrophobic groups in the nonionic surfactant wrap small solution particles, and while contacting the precipitant, the dispersibility of each active metal raw material can be improved, and the active components can be dispersed to the maximum extent, and the uniformity of the active metal in the catalyst can be improved, thereby increasing the metal loading in the catalyst and reducing the situation where the local active metal loading of the catalyst is low.
[0140] Comparative Example 4
[0141] This comparative example provides a composite metal oxide catalyst, the preparation method of which comprises:
[0142] 1. Use a measuring cylinder to take 400 mL of water and put it into a small beaker. Then add 2.1 g of nickel sulfate hexahydrate, 0.6 g of molybdenum sulfate pentahydrate, 1.8 g of magnesium sulfate hexahydrate, 2.1 g of aluminum sulfate nonahydrate, 0.5 g of copper sulfate trihydrate, and 0.5 g of chromium sulfate, and stir well at 80 °C to obtain a raw material solution.
[0143] 2. Take 11g of ammonium bicarbonate and dissolve it in 550ml of water to obtain a precipitant solution. Pour 100ml of the precipitant solution into a 2L three-necked flask, add the raw material solution to the precipitant solution at a rate of 450ml / h (peristaltic pump speed is 7) until the addition is complete to obtain a reaction solution, the pH value of the reaction solution is 9-10, and stir continuously at 85℃ until precipitation is complete.
[0144] 3. The reaction solution after precipitation was kept warm (85°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the crystallization temperature was set at 110°C. After drying, it was crushed with a mortar, sieved with an 80-mesh screen, and the sieved precursor was calcined at 800°C for 5 hours to obtain 1.36g of the target catalyst.
[0145] Calculated by the mass content of metal oxides, the catalyst contains 39% nickel, 7% chromium, 10% copper, 18% magnesium, 21% aluminum and 5% molybdenum.
[0146] Embodiment 6:
[0147] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0148] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Add 1.2 g of magnesium nitrate hexahydrate, 4.6 g of aluminum nitrate nonahydrate, and 0.6 g of lanthanum nitrate hexahydrate into the water. Stir thoroughly at 80°C to obtain the first solution.
[0149] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 3.3 g of nickel nitrate hexahydrate, 5.2 g of cobalt nitrate hexahydrate, and 15.6 g of polyoxyethylene lauryl ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0150] 3. The first solution and the second solution were dripped into a 2L three-necked flask to obtain a raw material solution; 11g of ammonium bicarbonate was dissolved in 550ml of water to obtain a precipitant solution, and the precipitant solution was dripped into the raw material solution at a rate of 450ml / h (peristaltic pump speed was 7) until the precipitant solution was completely dripped to obtain a reaction solution, the pH value of the reaction solution was 9-10, and stirring was continued at 90°C until precipitation was complete;
[0151] 4. The reaction solution after precipitation was kept warm (90°C) for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the drying temperature was set to 110°C. After drying, the solid was crushed with a mortar, sieved with an 80-mesh screen, and the sieved solid was calcined at 800°C for 5 hours to obtain 4.6g of the target catalyst.
[0152] Calculated by the mass content of metal oxides, the catalyst contains 50% cobalt, 20% nickel, 5% lanthanum, 4% magnesium and 21% aluminum.
[0153] Comparative Example 5:
[0154] This embodiment provides a composite metal oxide catalyst, the preparation method of which includes:
[0155] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Add 0.4 g of magnesium nitrate hexahydrate, 2.4 g of aluminum nitrate nonahydrate, and 0.2 g of lanthanum nitrate hexahydrate into the water. Stir thoroughly at 80°C to obtain the first solution.
[0156] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 1.1 g of nickel nitrate hexahydrate, 3 g of cobalt nitrate hexahydrate, and 9 g of alkylphenol polyoxyethylene ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0157] 3. The first solution and the second solution were dripped into a 2L three-necked flask to obtain a raw material solution; 11g of ammonium bicarbonate was dissolved in 550ml of water to obtain a precipitant solution, and the precipitant solution was dripped into the raw material solution at a speed of 450ml / h (peristaltic pump speed was 7) until the precipitant solution was completely dripped to obtain a reaction solution, the pH value of the reaction solution was 9-10, and stirring was continued at 60°C until precipitation was complete;
[0158] 4. The reaction solution with complete precipitation was kept warm (60°C) for aging for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for drying for 12 hours, and the drying temperature was set to 110°C. After drying, the solid was crushed with a mortar, sieved with an 80-mesh screen, and the sieved solid was calcined at 800°C for 5 hours to obtain 2.0g of the target catalyst.
[0159] Calculated by the mass content of metal oxides, the catalyst contains 62% cobalt, 14% nickel, 3% lanthanum, 3% magnesium and 18% aluminum.
[0160] Comparative Example 6:
[0161] This comparative example provides a composite metal oxide catalyst, the preparation method of which comprises:
[0162] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Add 2.7 g of magnesium nitrate hexahydrate and 8.6 g of aluminum nitrate nonahydrate into the water and stir thoroughly at 80°C to obtain the first solution.
[0163] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 2.1 g of nickel nitrate hexahydrate, 20.1 g of cobalt nitrate hexahydrate, and 5 g of alkylphenol polyoxyethylene ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0164] 3. The first solution and the second solution were dripped into a 2L three-necked flask to obtain a raw material solution; 11g of ammonium bicarbonate was dissolved in 550ml of water to obtain a precipitant solution, and the precipitant solution was dripped into the raw material solution at a speed of 450ml / h (peristaltic pump speed was 7) until the precipitant solution was completely dripped to obtain a reaction solution, the pH value of the reaction solution was 9-10, and stirring was continued at 85°C until precipitation was complete;
[0165] 4. The reaction solution with complete precipitation was kept warm (85°C) for aging for 8 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for drying for 12 hours, and the drying temperature was set to 110°C. After drying, the solid was crushed with a mortar, sieved with an 80-mesh screen, and the sieved solid was calcined at 800°C for 5 hours to obtain 10.5g of the target catalyst.
[0166] Calculated by the mass content of metal oxides, the catalyst contains 80% cobalt, 5% nickel, 4% magnesium and 11% aluminum.
[0167] Comparative Example 7:
[0168] This comparative example provides a composite metal oxide catalyst, the preparation method of which comprises:
[0169] 1. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Add 16.4 g of lanthanum nitrate hexahydrate into the water and stir thoroughly at 80°C to obtain the first solution.
[0170] 2. Use a measuring cylinder to take 200 mL of water and put it into a small beaker. Then add 19 g of nickel nitrate hexahydrate, 3 g of cobalt nitrate hexahydrate, and 5 g of alkylphenol polyoxyethylene ether respectively, and stir thoroughly at 80°C to obtain a second solution.
[0171] 3. The first solution and the second solution were dripped into a 2L three-necked flask to obtain a raw material solution; 11g of ammonium bicarbonate was dissolved in 550ml of water to obtain a precipitant solution, and the precipitant solution was dripped into the raw material solution at a speed of 450ml / h (peristaltic pump speed was 7) until the precipitant solution was completely dripped to obtain a reaction solution, the pH value of the reaction solution was 9-10, and stirring was continued at 85°C until precipitation was complete;
[0172] 4. The reaction solution with complete precipitation was kept warm (85°C) for 12 hours, and then the aged reaction solution was placed in an electric constant temperature blast drying oven for 12 hours, and the drying temperature was set to 110°C. After drying, the solid was crushed with a mortar, sieved with an 80-mesh screen, and the sieved solid was calcined at 800°C for 5 hours to obtain 12.3g of the target catalyst.
[0173] Calculated by the mass content of metal oxides, the catalyst contains 10% cobalt, 40% nickel and 50% lanthanum.
[0174] Test Example 1
[0175] The structure of the composite metal oxide catalyst prepared in Example 1 was characterized.
[0176] Figure 1a and Figure 1bThese are the mapping characterization results of Ni and Co of the composite metal oxide catalyst of Example 1. Figure 5a , Figure 5b They are the mapping characterization results of Ni and Co of the composite metal oxide catalyst of Comparative Example 3 respectively.
[0177] Will Figure 1a , Figure 1b , Figure 5a , Figure 5b Comparison shows that the nickel and cobalt in the catalyst of Comparative Example 3 without the addition of nonionic surfactants are significantly agglomerated, the catalyst active components have poor dispersibility and low effective loading; in contrast, the surface layer of the catalyst of Example 1 prepared by adding nonionic surfactants has uniformly distributed cobalt and nickel, and cobalt and nickel do not show obvious agglomeration. From the perspective of dispersion, the catalyst synthesized in Example 1 has high nickel and cobalt content and high dispersion, and the catalyst has many metal active sites per unit area, and the effective loading of active components is high.
[0178] Figure 2 The dark field transmission electron microscope image and element linear scanning image of the composite metal oxide catalyst of Example 1 are shown in FIG. Figure 2 It can be seen that the catalyst contains nickel and cobalt elements, and from the corresponding signal peaks, the internal metal active groups are evenly distributed. In the process of scanning from one edge to the other, the peaks of the corresponding elements did not fluctuate greatly, and the peak shape was stable, proving that the internal elements are evenly distributed and highly dispersed.
[0179] The crystal surface of the catalyst in Example 1 was characterized, and the results were as follows: Figure 4a , Figure 4b As shown. Figure 4a , Figure 4b It can be seen that there are more ordered crystal plane structures in the exposed crystal planes of the catalyst, which is conducive to the liberation of free carbon in the catalyst bulk phase and its precipitation from the surface after methane cracking, slowing down the deactivation of the catalyst due to carbon deposition and improving the carbon nanotube production capacity.
[0180] Example 7
[0181] This embodiment provides a methane catalytic cracking method, the method comprising:
[0182] 1. Pass hydrogen as reducing gas into a horizontal tube heating furnace filled with catalyst to reduce the catalyst. The reducing concentration of hydrogen is 10-45%, the reducing temperature is 300-900°C, and the reducing method is constant temperature reduction or synchronous temperature rise reduction;
[0183] 2. Methane is introduced into the horizontal tube heating furnace for vapor deposition reaction. The methane feed flow rate is 150-250 ml / min. The temperature of the vapor deposition reaction is 550-750° C. to obtain hydrogen and carbon nanotubes.
[0184] The catalyst used in the above method is the composite metal oxide catalyst of Examples 1 to 5 and Comparative Examples 1 to 5.
[0185] Figure 3a and Figure 3b The SEM and TEM images of the methane cracking products obtained using the catalyst of Example 1 are shown in FIG. Figure 3a and Figure 3b It can be seen that the methane cracking product is a carbon nanotube, which is a multi-walled carbon nanotube with a length of 10-20 μm and a diameter of 10-20 nm, which meets the standards of commercial carbon nanotubes, proving that the quality of the carbon nanotubes produced by the catalyst prepared by the present invention is high. The carbon nanotubes prepared in Examples 2 to 5 are also multi-walled carbon nanotubes with a length of 10-20 μm and a diameter of 10-20 nm, which meet the standards of commercial carbon nanotubes. The carbon nanotubes prepared by the catalysts of Comparative Examples 1 to 5 have a length of 0.5-10 μm and a diameter of 30-80 nm. Compared with the catalysts of Comparative Examples 1 to 5, the active components in the catalysts of each embodiment of the present invention are more dispersed, so the carbon nanotubes prepared have better morphology and better quality.
[0186] Table 1 summarizes the results of the above methods involving various catalysts. In the method corresponding to Table 1, the reduction concentration of hydrogen is 10%, the reduction temperature is 650°C, the reduction method is continuous reduction (i.e., synchronous temperature reduction), the methane feed flow rate is 200 ml / min, and the temperature of the vapor deposition reaction is 680°C.
[0187] In Table 1, the calculation method for the maximum conversion rate of methane is
[0188]
[0189]
[0190] Where X is the conversion rate, t is the reaction time, C H2 It is the instantaneous hydrogen concentration displayed by the three-phase gas analyzer.
[0191] The catalyst life is the time from when the methane conversion rate starts to increase to when it drops below 5%.
[0192] Table 1
[0193]
[0194] The catalysts of Comparative Examples 1 and 4 do not contain Co. By comparing the results of Comparative Examples 1 and 4 with those of Examples 1 to 6, it can be seen that by adding cobalt as the main active component for dehydrogenation in the catalyst, the methane conversion rate of the catalyst can be improved, the carbon nanotube yield can be increased, and the service life of the catalyst can be extended.
[0195] No nonionic surfactant was added during the catalyst preparation process of Comparative Examples 2 to 4, and the amount of nonionic surfactant used in Comparative Example 5 was too small. Comparing the results of Comparative Examples 3 to 5 with those of Examples 1 to 6, it can be seen that by adding a nonionic surfactant during the catalyst preparation process and controlling the added amount within a suitable range, the dispersion of active metals can be improved, the methane conversion rate can be improved, and the service life of the catalyst can be extended.
[0196] No dehydrogenation-promoting active component was added in Comparative Example 6. By comparing the results of Comparative Example 6 with those of Examples 1 to 6, it can be seen that by adding a dehydrogenation-promoting active component to the catalyst, the dispersion of the active metal can be improved and the service life of the catalyst can be greatly extended.
[0197] No carrier was added in Comparative Example 7. By comparing the results of Comparative Example 7 with those of Examples 1 to 6, it can be seen that adding a carrier to the catalyst helps to improve the dispersion of the active metal and extend the service life of the catalyst.
[0198] From the above results, it can be seen that the life of the catalyst prepared by the present invention can reach 4h-9h, and the maximum methane conversion rate can reach 27.8%-45.9%. The catalyst provided by the present invention is applied to the methane catalytic cracking process, which can effectively increase the yield of carbon nanotubes, obtain high-quality carbon nanotubes, and has a high methane conversion rate and a long catalyst life.
Claims
1. A composite metal oxide catalyst, wherein: Taking the total mass of the catalyst as 100%, the catalyst comprises 10%-80% of a main dehydrogenation active component, 5%-50% of a dehydrogenation auxiliary active component, and the remainder is a carrier; The metal element in the dehydrogenation auxiliary active component is selected from one or more combinations of the fourth period, the fifth period, and the sixth period and is selected from one or more combinations of the IB group, the VB group, the VIB group, and the VIIB group; and / or, the metal element in the dehydrogenation auxiliary active component is selected from La-based metals; The raw material of the composite metal oxide catalyst includes a non-ionic surfactant, and the mass ratio of the dehydrogenation main active component to the non-ionic surfactant is 1:3 to 1:
6.
2. The catalyst according to claim 1, wherein The metal element in the dehydrogenation main active component is selected from Group VIII of the fourth period; Preferably, the metal element of the dehydrogenation main active component includes cobalt.
3. The catalyst according to claim 1 or 2, wherein The mass of the dehydrogenation main active component is 15%-50% of the total mass of the catalyst.
4. The catalyst according to claim 1, wherein The mass of the dehydrogenation auxiliary active component is 14%-42% of the total mass of the catalyst.
5. The catalyst according to claim 1 or 4, wherein The metal elements in the dehydrogenation auxiliary active component include one or a combination of two or more of La, Cr, Mo, Ce and Cu.
6. The catalyst according to claim 1, wherein The nonionic surfactant includes one or a combination of two or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester and polyoxyethylene alkylamine.
7. The catalyst according to any one of claims 1 to 6, wherein Based on the total mass of the catalyst being 100%, the catalyst further comprises 5% to 40% of a secondary active component, wherein the metal element in the secondary active component is selected from Group VIII of at least one of the fourth period, the fifth period, and the sixth period; Preferably, the mass of the secondary active component is 20%-35% of the total mass of the catalyst; Preferably, the metal element in the secondary active component includes one or a combination of two or more of Fe, Ni, Pd, Pt and Ru.
8. A method for preparing the composite metal oxide catalyst according to any one of claims 1 to 7, comprising: S1, mixing a carrier precursor, a precursor of a dehydrogenation auxiliary active component, a precursor of a dehydrogenation main active component, and a non-ionic surfactant to form a raw material solution; S2. Add the precipitant dropwise to the raw material solution to form a reaction solution, or add the raw material solution and the precipitant dropwise in parallel to form a reaction solution; the reaction solution is precipitated, and after the precipitation is complete, it is aged, dried, and calcined to obtain a composite metal oxide catalyst.
9. The preparation method according to claim 8, wherein: The raw material solution also includes a precursor of a secondary active component; Preferably, the precursor of the secondary active component, the nonionic surfactant and the primary active component are added simultaneously.
10. The preparation method according to claim 8, wherein: The pH of the reaction solution is 9-10.
11. The preparation method according to claim 8, wherein: The precipitation and / or aging temperature is 60-90° C., and the aging time is 4-12 hours; Preferably, the precipitation and / or aging temperature is 70-85°C; Preferably, the aging time is 6-8h.
12. The preparation method according to claim 8, wherein: The dropping speed of the raw material solution and / or precipitant is 60-600 ml / h, preferably 300-500 ml / h.
13. A methane catalytic cracking method, wherein the catalyst used in the methane catalytic cracking method comprises the composite metal oxide catalyst according to any one of claims 1 to 7, and the cracking products of the method comprise carbon nanotubes and hydrogen.
14. The methane catalytic cracking method according to claim 13, wherein: The methane feed flow rate is 50-300 ml / min, the concentration of reducing gas is 5%-80%, the reduction temperature is 300-900°C, and the reaction temperature is 500-800°C; Preferably, the methane feed flow rate is 150-250 ml / min; Preferably, the reducing gas concentration is 10-45%; Preferably, the reduction temperature is 550-750°C; Preferably, the reaction temperature is 550-750°C.
Citation Information
Patent Citations
Bifunctional catalyst for methane catalytic cracking, preparation method thereof and hydrogen production method
CN105013506A
Supported catalyst, preparation method therefor, application of supported catalyst and method for preparing syngas through dry reforming of methane
CN109718799A
Methane cracking catalyst and preparation method thereof
CN111185179A
Nickel-gallium alloy catalyst as well as preparation method and application thereof
CN112705208A
Cited By
Carbon dioxide methanation and methane cracking coupled carbon sequestration power generation system and method
CN121130784A
Carbon dioxide methanation coupled with methane cracking for carbon capture and power generation system and method
CN121130784B
Dual-aid composite carrier catalyst and preparation method thereof
CN122076453A